Reinforced concrete structures: A review of corrosion mechanisms and advances in electrical methods for corrosion monitoring. (1st February 2021) - Rodrigues, Romain; Gaboreau, Stéphane; Gance, Julien; Ignatiadis, Ioannis; Betelu, Stéphanie
Highlights: Non-uniform corrosion is expected irrespective of the depassivation mechanism. Corrosion rate is mainly dependent on water content, temperature and pore-size distribution. Concrete resistivity affects the current distribution when measuring corrosion rate. Electrical tomography is of prime interest to account for concrete heterogeneity. Monitoring of non-uniform corrosion in four-electrode configuration is promising. Abstract: Steel corrosion is the main cause of deterioration of reinforced concrete (RC) structures. We provide an up-to-date review on corrosion mechanisms and recent advances in electrical methods for corrosion monitoring. When assessing corrosion mechanism, the inherent heterogeneity of RC structures and the significant effect of environmental factors remain major issues in data interpretations. The steel surface condition and local inhomogeneities at the steel–concrete interface appear to have an important effect on corrosion initiation. Considering uniform corrosion in atmospherically exposed RC structures, the two main influencing factors of the corrosion process are the water content and the pore structure at the steel–concrete interface. However, irrespective of the depassivation mechanism, i.e. carbonation or chloride-induced corrosion, non-uniform corrosion is expected to be the main process for RC structures due to local variations in environmental exposure or the presence of interconnected rebars with different properties. Future studies may then be focused on their effect on macrocell corrosion to gain further insights in the corrosion mechanisms of RC structures. Concerning corrosion monitoring using electrical methods, the half-cell potential technique with potential mapping is accurate for locating areas with a high corrosion risk. Recent developments in the measurement of concrete resistivity have shown that the use of electrical resistivity tomography allows to consider appropriately the inherent heterogeneity of concrete and provides more insights on transport phenomena (e.g. water and salts ingress) in the material. Nevertheless, during the corrosion propagation stage, the polarization resistance remains the most important parameter to be determined as it provides quantitative information of the corrosion rate. If conventional three-electrode configuration methods can supply an accurate determination in the case of uniform corrosion, they often fail in the case of macrocell corrosion in field experiments. Recent advances have shown that a four-electrode configuration without any connection to the rebar can rather be used for the non-destructive testing and evaluation of corrosion. If studies are still required to quantify the corrosion rate, this method appears sensitive to localized corrosion and thus more suitable to field investigations. Finally, the coupling of numerical simulations with complementary electrical and other non-destructive testing methods is essential for consolidating the results to provide a better diagnosis of the service life of RC structures.